GENOMIC ANALYSIS OF SARS-COV-2 OMICRON VARIANT IN WEST JAVA ON JANUARY - FEBRUARY 2022 - Rafi Ibrahim, Sulthan
COVID-19 is an upper respiratory tract disease that is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus and has caused a global pandemic. SARS-CoV-2 has a high mutation rate which makes the current treatment strategies ineffective due to the emergence of new variants. One of the most common methods used to determine mutations in the viral genome is to perform a whole genome sequencing (WGS). West Java Health Laboratory is one of the government facilities that has conducted mass sequencing on samples from various regions in West Java. However, not many studies have conducted detailed molecular analysis of these samples. It is known that molecular analysis can be used to monitor mutation patterns that occur in various SARS-CoV-2 samples. Therefore, this study focuses on detailed molecular analysis on samples of SARS-CoV-2 from West Java, especially on Omicron variant samples which is one of the most recent and infectious SARS-CoV-2 Variant of Concern (VOC). The SARS-CoV-2 sequences was taken from the GISAID database in the January-February 2022 period with the keyword “WJHL”, then the sequences were aligned with the reference sequence Wuhan-Hu-1. Phylogenetic analysis was performed using the Neighbor-joining method. The spike protein model was constructed with the i-TASSER webserver using the consensus sequences for Omicron, Delta, and wildtype variants. Molecular docking analysis was performed with the PRODIGY webserver. In this study, 342 Omicron samples, 89 Delta samples and 1 wildtype sample were used. The analysis results showed that the Omicron variant had a significantly higher mutation rate than the Delta and wildtype variants (p<0.05). Most of the mutations in the Omicron variants occurred in the S, N, and M genes. Phylogenetic analysis using the whole genome sequence, spike, M, and N genes showed that the Omicron and Delta variants belonged to different clades due to unique mutation in each variant. But phylogenetic analysis using the N and M genes could not be used to differentiate the existing Omicron sub-variants. Mutations that occur in the structural proteins tend to stabilize the protein structure, while mutations in non-structural proteins tend to destabilize the protein structure. Molecular docking analysis showed that Omicron had a higher binding affinity than the Delta variant. From this study, it was concluded that the Omicron variant had a higher mutation rate and a higher binding affinity with the ACE2 receptor, and a different mutation profile with the Delta variant. The results of this study are expected to be used to determine the mutational profile of the Omicron variant that occurs in West Java, and as a reference for further genomic surveillance studies at both national and global levels.